Comparison of OCT Angiography Parameters after Administration of Intravitreal Brolucizumab versus Ranibizumab in Exudative Age-related Macular Degeneration - Sanjitha Vilma Moses; Aadithreya Varman; Dinesh Balakumar; Arulmozhi Varman (TNOA Journal of Ophthalmic Science and Research)
Purpose: To compare the OCT angiography (OCTA)–derived parametric changes before and after intravitreal administration of ranibizumab and brolucizumab in patients with neovascular age-related macular degeneration (ARMD) and to compare the changes between the two groups. Methods: This retrospective cohort study was done on 68 eyes with neovascular ARMD: 34 received injection ranibizumab and 34 received brolucizumab in a stratified manner. Central foveal thickness (CFT) and OCTA parameters like vessel density (VD), superficial capillary plexus (SCP), deep capillary plexus (DCP), foveal avascular zone, (FAZ), fractal dimension (FD) were assessed. The scans were repeated 1 month postinjection. Results: In total, 46% had type 1 CNVM and 54% had Type 2 CNVM. In both the ranibizumab and brolucizumab group, the corrected visual acuity showed comparable significant improvement 1 month postinjection. The CFT showed significant reduction in both, more significant in brolucizumab. OCTA showed a minimal nonsignificant reduction in the VD, SCP and DCP at 1 month, which were not significantly different. The FAZ and FD showed a significant increase and reduction, respectively, in the brolucizumab group, unlike the ranibizumab group. Conclusion: OCTA changes suggest that anti-VEGF drugs produce no change in the capillary density. A reduction in structural architecture of smaller capillary branches i.e. fractal dimension and increase in FAZ is noted with brolucizumab, suggesting that some structural alterations of retinal microvasculature do exist with the drug.